Canalization and Creative Evolution: Images of Life in Bergson and Whitehead - Posteraro, Tano (Das Questões, 2019)
Whitehead famously wrote that the status of life in nature constituted the modern problem both of philosophy and science. But Bergson could just as easily have penned those words. Indeed, his Creative Evolution stands as one of the most serious engagements with the problem of life in recent philosophical history. Life, for Bergson, was to be thought of as a kind of impetus, a drive or force. But he insisted that this was only an image borrowed from psychology, the best one available, but an image no less. This is because images are essential to the organization of scientific discourse and practice. We think through them, use them not only as explanatory aids, but as callipers first: without them, we are unable to grasp and articulate our objects of study, even before the endeavour to communicate what it is that we have managed to grasp. Perhaps most famous of the various images that animate Creative Evolution is that of the canal, or canalization. It is striking that this image managed to find its way, through Whitehead’s Process and Reality, into modern embryology, where it continues to serve as an image for the way epigenetic landscapes operate in order to bring about, or canalize, a small number of end results form a large number of developmental potentialities. This paper briefly traces the history of that image from out of Bergson’s philosophy of life, through Whitehead’s creative metaphysical appropriation of it, and into the embryology of C.H. Waddington. In order to make sense of that history, I do three things: first, I situate the image of the canal in Bergson’s Creative Evolution, elucidating its context and aims; second, I demonstrate its utility for Whitehead’s metaphysics, the new purposes for which it was deployed; and third, I argue that it was this latter reconfiguration of the concept that prepared it for its enlistment as a key moment in embryological explanation. I claim that the canal occupies a privileged position in Bergson’s philosophy of life, for it is an image of life that is turned against itself as an image, meant to demonstrate the limits of imagistic thought. I conclude the paper with a series of comments on this suggestion: that it was the image of the canal that found its way into modern embryology tells us something important about the relation between science and philosophy, or between image and imagination, matter and life. On these points, Bergson and Whitehead converge on a novel philosophy of nature that is capable both of responding to scientific discoveries as well as of accommodating them within an enlarged process-oriented metaphysics.